Interplay between phase separation and gel formation in stirred acid milk/guar gum gels: Effect of acidification rate. Issue 9 (September 2014) - Rohart, Anne; Moulin, Gabrielle; Michon, Camille; Mackie, Alan
ABSTRACT The possibility of designing various microstructures through the interplay between phase separation due to depletion mechanisms and acid‐induced protein gelation was investigated. To modify the phase separation and gelation kinetics, guar gum/acid milk mixtures were acidified using glucono‐δ‐lactone at temperatures varying from 30 to 60°C. The microstructures of the stirred mixed gels were then discussed in light of the knowledge of the phase separation and gelation timescales. Small spherical protein‐enriched micro‐gels dispersed in a guar gum‐enriched continuous phase were found at high acidification temperatures, suggesting that the protein acid gelation kinetics was quicker than an extensive droplet growth through phase separation. For lower acidification temperatures, a region where droplet coalescence and sedimentation competed with gel formation was identified. Thus, depending on the residence time in that temperature domain, the resulting microstructures varied from spherical to extended filaments of more than 100 μm length. The results demonstrated that a broad range of defined microstructures can been created by triggered arrest through gelation of the phase‐separating structure. © 2014 Wiley Periodicals, Inc. Biopolymers 101: 966–974, 2014.